Radiative conduction problem in the thin layer of semi-transparent medium. The weak absorption case - Kolesnikov, A.V.; Virchenko, Yu.P. (Functional Materials, 2007)
Heat conduction problem in the thin layer of semi-transparent media is studied. Together with mechanism of ordinary thermal conductance, the energy transfer by electromagnetic irradiation is taked into account. The Stefan-Boltzmann irradiation law is used. The case of small energy absorption has been studied. It corresponds to small value of the optical length λ. First terms of the asymtotic expansion on λ powers of the stationary temperature ditribution in the layer are obtained.